Utility of peripheral intravenous cannulae inserted in one tertiary referral emergency department: A medical record audit. Issue 1 (February 2016) - Fry, Margaret; Romero, Bernadine; Berry, Alison
Summary: Introduction: Peripheral intravenous cannulation is a common intervention performed within the Emergency Department (ED). However, studies have shown that while patients may have a cannulae inserted they are often unused. Across Australia, it is unclear the frequency and use of peripheral intravenous cannulae (PIVC) within the emergency setting. Method: A one-month retrospective randomised medical record audit of adult patients was conducted. Data were retrieved from the ED electronic database and the paper medical record. Data included: patient demographic (age, gender) and clinical information (time of arrival, triage category, presenting problem, discharge diagnostic code, and disposition) and cannula usage (time of fluids, pharmacological agents, pathology, radiological investigations, other diagnostic uses). Results: Of the 357 patients, 209 (58.5%) had a peripheral intravenous cannula inserted. Of the 209 patients a total of 233 cannulae were inserted. Of the patients with a cannulae 190 (90.9%) were used within 72 h. The majority of cannulae (68.9%; n = 131) had more than one medical intervention. Conclusion: The majority of PIVCs inserted during the ED visit were used for medical treatment. The majority of devices were used for intravenous fluids medications and were accessed for multiple interventions. For future audit purposes improved documentation of this procedure is needed.